information-didactic basis for the formation of common cultural competences of bachelors of technique and technologies by facilities of foreign language - Irina V. Vlasova; Arina V. Banartseva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article discusses a set of cultural competencies that should be possessed by graduates of the technical University, as well as requirements to the levels of their development. It also presents information-didactic basis for the formation of common cultural competences in the process of teaching students a foreign language, the structure of which contains: a basic textbook for students of engineering and technology in foreign language, package interdisciplinary educational complexes, scientific and popular scientific journals, Internet resources in this subject area. The article gives a short description of a basic textbook, intended for the professional education of English for students of speciality 020201 "Fundamental and applied chemistry", a profile of preparation is "Pharmaceutical chemistry" of the chemical-technological faculty.